2014
DOI: 10.4236/jbnb.2014.51002
|View full text |Cite
|
Sign up to set email alerts
|

Propyl-Sulfonic Acid Functionalized Nanoparticles as Catalyst for Pretreatment of Corn Stover

Abstract: Propyl-sulfonic (PS) acid-functionalized nanoparticles were synthesized, characterized and evaluated as catalysts for pretreatment of corn stover. Silica coated nanoparticles were functionalized with 0.5% mercaptopropyltrimethoxysilane (MPTMS) at neutral pH in a mixture of water and ethanol. Sulfur contents of the acid functionalized nanoparticles, measured in a CHNS analyzer, varied from 6%-10%, and the acid load ranged from 0.040 to 0.066 mmol H + /g. A Box-Behnken design was employed to calculate the minimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 45 publications
(55 reference statements)
2
14
0
1
Order By: Relevance
“…Several physical and chemical pre-treatments using heat, acids, bases, organic solvents and ionic liquids have been developed and studied extensively. Although, chemical pre-treatment techniques are attractive due to the higher reaction efficiency and excellent mass transfer capabilities (Guo et al, 2012), use of chemical agents leads to various environmental issues and also requires expensive unit operations on the downstream side of the process (Peña et al, 2014). Therefore, reusable pre-treatment agents that also minimise environmental impacts are required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several physical and chemical pre-treatments using heat, acids, bases, organic solvents and ionic liquids have been developed and studied extensively. Although, chemical pre-treatment techniques are attractive due to the higher reaction efficiency and excellent mass transfer capabilities (Guo et al, 2012), use of chemical agents leads to various environmental issues and also requires expensive unit operations on the downstream side of the process (Peña et al, 2014). Therefore, reusable pre-treatment agents that also minimise environmental impacts are required.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, solid acid catalysts allow for simple separation from products by vacuum filtration or magnetic separation (Lai et al, 2011;Guo et al, 2013;Peña et al, 2014). Further, the catalysts may be used repeatedly for the reaction without neutralisation, therefore decreasing energy consumption and waste (Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in another study, Pena et al . demonstrated the catalytic efficiency of a nanocatalysts, i.e.…”
Section: Nanotechnology For the Pretreatment Of Lbmentioning
confidence: 75%
“…Acid‐functionalized nanoparticles are also referred to as solid acid nanocatalysts; these catalysts have a strong ability to catalyze hydrolysis reactions. It has been demonstrated that acid‐functionalized magnetic nanoparticles could have a similar catalytic effect to mineral acids (used in chemical pretreatment methods) during biomass pretreatment, with the added advantage that these nanoparticles are recoverable and reusable due to their strong magnetic nature . Recycling and reuse of the pretreatment nanocatalysts will be helpful in minimizing the process cost due to minimum downstream processing requirements.…”
Section: Nanotechnology For the Pretreatment Of Lbmentioning
confidence: 99%